Synthesis and magnetism of hematite and maghemite nanoparticles - Woo, Kyoungja; Lee, Ho Jin (ELSEVIER SCIENCE BV, 2004)
Rod-shaped hematite and maghemite nanoparticles with diameters of 5 nm and lengths of 16 and 17 nm were synthesized by a newly designed sol-gel mediated reaction and their magnetic properties were investigated. The hematite nanorods showed ferromagnetic behavior from 5 to 300 K, while the maghemite nanorods exhibited superparamagnetic behavior with a blocking temperature at around 130 K. (C) 2003 Elsevier B.V. All rights reserved.